“Miroirs et Reflets” by Gabriel Iranyi – An Auditory Metaphor of Visual Interactions - MAGAZIN, Alexandra (Studia Universitatis Babes-Bolyai Musica, 2024)
The work Miroirs et reflets by composer Gabriel Iranyi, explores the concept of mirroring and reflection in both technical and metaphorical ways. Iranyi was inspired by the visual art of Claude Monet and Paul Klee, translating principles of reflection, symmetry, and heterophony into his musical composition. The piece is structured in two distinct parts, with the first section characterized by a static and rigorous approach, and the second part defined by spontaneity and fast tempo. Iranyi uses various compositional techniques, such as isolated sustained sounds, pitch shifts, harmonics, and convex motion, to create an auditory metaphor for visual interactions. The work aims to engage the listener and performer in an artistic exploration that adds depth to the musical motifs.